Comprehensive characterization and validation of the Prp-hPFN1G118V mouse model: Guidelines for preclinical therapeutic testing for ALS - Kaly A. Mueller; Emma G. Suneby; Matthew H. Ferola; Andy J. Moreno; Joshua D. Kidd; Kenneth Thompson; Fernando G. Vieira; Gregorio Valdez; Theo Hatzipetros (Neurobiology of Disease)
The hPFN1G118V mouse model, overexpressing mutant human profilin1 linked to a rare form of ALS, was comprehensively characterized to assess its suitability for preclinical drug testing. Using a large cohort of nearly 250 transgenic and wild-type mice in a longitudinal study, we combined behavioral, electrophysiological, and neuropathological assessments to define the chronology of pathological events and assess inherent subject variability. The early stage of the disease in this model was characterized by elevated plasma neurofilament light chain levels, an effect that persisted and progressed throughout the course of the disease, followed by spinal cord neuroinflammation, suggesting that axonal pathology is the initiating event. The middle stage of the disease involved progressive neuromuscular decline, including reductions in compound muscle action potential (CMAP) and grip strength, accompanied by neuromuscular junction degeneration. The end-stage of the disease was characterized by the onset of visible changes such as weight loss, gait abnormalities and hindlimb paresis that quickly progressed to paralysis. At end-stage we also observed spinal motor neuron loss and TDP-43 pathology. The average humane endpoint was 213 days for females and 237 days for males. Our findings demonstrate that hPFN1G118V mice recapitulate key ALS features with moderate disease progression and a reproducible disease course, making them a valuable model for therapeutic testing. Recommendations are provided to optimize study design for preclinical testing, emphasizing survival duration as the primary endpoint, with CMAP and plasma NFL as key secondary readouts.